Decolonizing music education: Moving beyond tokenism. (August 2015) - Hess, Juliet
Current music education curricula across Canada designate Western classical music as the music most worthy of study through emphasis on elements of music that are decidedly Western. Despite the way the curriculum is constructed, many music teachers strive to create diverse programs for their students. In her examination of women's studies programs, Chandra Talpade Mohanty (2003) puts forward three curricular models that describe the manner in which "Other" subject material is engaged in the curriculum within the discipline of women's studies. I rethink her pedagogical models and apply them to music education. Mohanty's first two models are more tokenistic in nature while the third model is comparative. While there are benefits to the first two models, the third, when applied to music, reveals that musics are better understood relationally. Mohanty's (2003) third pedagogical model has much to offer music education.